Asymmetric synthesis of N,O,O,O-tetra-acetyl D-lyxo-phytosphingosine, jaspine B (pachastrissamine) and its C(2)-epimer - Abraham, E; Candela-Lena, J; Davies, S; Georgiou, M; Nicholson, R; Roberts, P; Russell, A; Sanchez-Fernandez, E; Smith, A; Thomson, J (2007)
The highly diastereoselective conjugate addition of lithium (S)-N-benzyl-N-(α-methylbenzyl)amide to a γ-silyloxy-α,β-unsaturated ester and in situ enolate oxidation with (+)-(camphorsulfonyl)oxaziridine has been used as the key step in the asymmetric synthesis of N,O,O,O-tetra-acetyl d-lyxo-phytosphingosine, jaspine B (pachastrissamine) and its C(2)-epimer. © 2007 Elsevier Ltd. All rights reserved.